IMPROVING THE RESULTS OF GRADE V STUDENTS IN SCIENCE LESSONS WITH THE FOOD CHAIN AND FOOD WEBS MATERIAL THROUGH AUDIO VISUAL AT ELEMENTARY SCHOOL 3 KARANGANYAR - Aribowo, Agus; Azmi, Ulil (Academic Journal Research, 2024)
Objective: This study aims to enhance the academic performance of fifth-grade students in understanding food chains and food webs through the implementation of audio-visual media at UPTD SDN 3 Karanganyar. Initial data revealed that only 21.73% of students (5 out of 23) met the competency threshold, with an average class score of 41.73. Method: Conducted as a Classroom Action Research (CAR) study, the research spanned two cycles, each consisting of planning, implementation, observation, and reflection phases. The study involved 23 fifth-grade students. Results: The integration of audio-visual media resulted in significant improvements in students’ learning outcomes. The average score increased from 57.39% in Cycle 1 to 89.56% in Cycle 2, indicating substantial enhancement in students' comprehension of food chains and food webs. The use of audio-visual tools fostered an interactive and engaging learning environment, promoting active participation and deeper understanding. Novelty: This research highlights the effectiveness of audio-visual media as an innovative pedagogical tool for improving science education outcomes in elementary schools. It emphasizes the role of interactive media in enhancing conceptual understanding and recommends its broader application in similar educational settings.